Analysing the acceptance and impact of artificial intelligence in higher education: A systematic review - Rinrin Meilani, Salim; Nur Shamsiah, Abdul Rahman; Noor Azida, Sahabudin (IEEE, 2025)
It is concerning that Artificial Intelligence (AI) is developing so quickly. Education is one of the parts affected by the presence of AI. AI can be utilized by students in learning activities, doing assignments, and answering academic questions. Previous research recommends looking at the acceptance and impact of AI on learning performance, so this study tries to conduct a literature review to resolve this gap. This research was conducted using the PRISMA method with initial literature of 708 papers sourced from IEEE, Science Direct, Scopus, Springer, and WOS. After the screening process, 22 articles were finally in accordance with this research. The findings of the literature results from the studies that have been conducted state that AI in Education has a positive impact. AI is accepted and utilized by students because it can improve their academic abilities, solve problems and support academic achievement. However, it was found that there was still anxiety in the use of AI. Therefore, educational institutions are required to design policies in implementing AI in the curriculum so that AI can be used properly to support improved learning.